1989
DOI: 10.1203/00006450-198911000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperoxia on Antioxidants in Neonatal Rat Type II Cells in Vitro and in Vivo

Abstract: ABSTRACT. Relative resistance to oxygen toxicity in newborn animals (compared to adults) has been associated with increased antioxidant enzymes and glutathione in lung homogenate. The cell type(s) involved in this increase is unknown. We investigated the effect of hyperoxia in vitro and in vivo on the following antioxidants (superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glucose-6-phosphate dehydrogenase, and glutathione) in alveolar type I1 cells from neonatal rats. Type I1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…In neonatal type I1 cells, our findings of a marked increase in SOD in neonatal type I1 cells after hyperoxic exposure differ from those of Kennedy et al (8), who reported decreases in CAT and no changes in SOD and GPX activities in neonatal type I1 cells after 4 d of exposure to >95% 02. Methodologic differences that could account for these results include oxygen concentration, duration of exposure, and method of type I1 cell isolation (trypsin versus elastase).…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…In neonatal type I1 cells, our findings of a marked increase in SOD in neonatal type I1 cells after hyperoxic exposure differ from those of Kennedy et al (8), who reported decreases in CAT and no changes in SOD and GPX activities in neonatal type I1 cells after 4 d of exposure to >95% 02. Methodologic differences that could account for these results include oxygen concentration, duration of exposure, and method of type I1 cell isolation (trypsin versus elastase).…”
Section: Resultscontrasting
confidence: 57%
“…However, this has not been reported to occur with elastase in regard to the antioxidant enzymes (6). The decrease in cell yield from oxygen-exposed animals noted in the present study has been previously reported (6)(7)(8) and attributed to difficulties of protease digestion of edematous lung. However, isolation of a selected cell population after hyperoxic exposure cannot be totally excluded.…”
Section: Resultsmentioning
confidence: 34%
See 2 more Smart Citations
“…The modified procedure yielded 1-2 x lo6 cells per pup with a purity of 83-87% compared with a range of 1-3 x 1 O6 cells per pup and purity of 85-95 % previously reported by others for 1-wk-old rats (2 1, 22). The reasons for the slightly lower purity observed in the present study are not clear but may be related to a number of factors such as the original number of cells plated, available surface area of culture flask, adhesive properties of the flask, age of animals, concentrations of trypsin used for cell isolation, and identification of type I1 cells on the basis of the appearance of lamellar body, which is dependent on the maturity of the cells (22)(23)(24). Nevertheless, using the modified procedure it was possible to process four to eight rat pups in a single isolation to provide sufficient numbers of cells for subsequent metabolic studies.…”
Section: Discussionmentioning
confidence: 74%